Enhancing bass effect in modern LCD TV - Liew, Justin Soon Jiat. (2012)
This report writes on the progress of learning and assembling a Virtual Bass System (VBS). A VBS (VBS #1) which is pre-assembled in a Texas Instrument C5509A DSP was studied and the essential features of this VBS are transferred to another VBS (VBS #2) in a form of a Texas Instrument C5505 eZdsp USB stick. Observations on both VBSs are included and the conclusion of the project will be shown in the last section.